Evaluation of Information Technology Governance Using BAI Domain In Hospital - Fernando, Erick (Publisher Cv. Inara, 2023)
The governance of information technology in hospitals is a crucial component in facilitating the alignment of information technology initiatives with the strategic objectives of XYZ hospital, thereby contributing to the achievement of its organizational goals. XYZ hospital is currently facing a number of challenges, one of which pertains to the Information System utilized for delivering services to visitors. The resolution of this problem can be achieved through the implementation of an assessment using the Cobit 5 framework, specifically targeting the BAI domain. This approach aims to offer recommendations for enhancing the value of capability levels, thereby improving information technology governance within the hospital setting. The results of the investigation conducted on the evaluation of information technology governance utilizing the Cobit 5 framework at